2016
DOI: 10.18632/oncotarget.12754
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of Wnt/β-catenin pathway genes are associated with the efficacy and toxicities of radiotherapy in patients with nasopharyngeal carcinoma

Abstract: Radiotherapy (RT) is the normative therapeutic treatment for primary nasopharyngeal carcinoma (NPC). Single nucleotide polymorphisms (SNPs) of genes in Wnt/β-catenin pathway are correlated to the development, prognosis, and treatment benefit of various cancers. However, it has not been established whether SNPs of Wnt/β-catenin pathway are associated with nasopharyngeal tumorigenesis and the efficacy of RT in NPC patients. Therefore, in this study, we aimed to investigate the nine potentially functional SNPs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Song et al [ 37 ] reported that Wnt/beta-catenin was also an oncogenic pathway targeted by H. pylori in gastric carcinogenesis. Genetic polymorphisms of Wnt/beta-catenin pathway genes are also associated with the susceptibility, survival, efficacy and toxicities of radiotherapy of multiple cancers [ 39 45 ]. In current study, we found the expression level of circ-ITCH in HCC tissues was significantly lower than the level in adjacent tissues, which indicated that circ-ITCH worked as an tumor suppressor gene for carcinogenesis of HCC, consistent with its function in ESCC, colorectal cancer, and lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Song et al [ 37 ] reported that Wnt/beta-catenin was also an oncogenic pathway targeted by H. pylori in gastric carcinogenesis. Genetic polymorphisms of Wnt/beta-catenin pathway genes are also associated with the susceptibility, survival, efficacy and toxicities of radiotherapy of multiple cancers [ 39 45 ]. In current study, we found the expression level of circ-ITCH in HCC tissues was significantly lower than the level in adjacent tissues, which indicated that circ-ITCH worked as an tumor suppressor gene for carcinogenesis of HCC, consistent with its function in ESCC, colorectal cancer, and lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of data from patients with head and neck cancer demonstrated a correlation between SNPs of genes: TGFB1 and XRCC1a (C allele of gene TGFB1 [T869C codon 10 Leu/Pro, rs1982073], A allele of the gene XRCC1 [G28152A, codon 399 Arg/Gln, rs25487]) and the intensity of late skin reactions. 8 The correlation was also confirmed between oral mucositis intensification, including dysphagia, and the healing process, [9][10][11][12] Intensification of dysphagia was also found in patients with one allelic variation of Wnt/b-catenin GSK3b (rs375557) gene and recessive variant of adenomatous polyposis coli gene (rs454886) polymorphisms. 13 The hypothesis of our study is that ghrelin is a potential factor modifying the cell nutrition status, local inflammatory process, and intensification of postirradiation reaction and that SNPs of the ghrelin coding gene (GHRL) are responsible for individual variability in oral mucositis intensification.…”
Section: Introductionmentioning
confidence: 81%
“…The analysis of data from patients with head and neck cancer demonstrated a correlation between SNPs of genes: TGFB1 and XRCC1a (C allele of gene TGFB1 [T869C codon 10 Leu/Pro, rs1982073], A allele of the gene XRCC1 [G28152A, codon 399 Arg/Gln, rs25487]) and the intensity of late skin reactions . The correlation was also confirmed between oral mucositis intensification, including dysphagia, and the healing process, and SNPs of DNA repair genes (eg, genotypes CT/TT [c.722] and CG/GG [Ku70c‐1310] of XRCC3 gene and allele C of the ERCC4 [T2505C] gene as well as SNPs of XRCC1 [c.1196A>G; allele A] and RAD51 [c.‐3429G>C] allele C genes) . Intensification of dysphagia was also found in patients with one allelic variation of Wnt/β‐catenin GSK3β (rs375557) gene and recessive variant of adenomatous polyposis coli gene (rs454886) polymorphisms …”
Section: Introductionmentioning
confidence: 85%
“…To date, many studies were trying to evaluate the correlation between genetic variants and radiosensitivity and the reaction of normal tissues to irradiation. However, most of the studies assessing the association of SNPs with OM are focused on the following processes: DNA repair, oxidation and stress response, apoptosis [14], embryogenesis [27], as well as inflammation [14], and only one (our previous paper) concerned TNF-α -TNFR axis [28].…”
Section: Discussionmentioning
confidence: 99%